Frank-Walter Steinmeier: Eine politische Biographie - Kohlmann, Sebastian (transcript, 2017)
This biography is the first biography to analyze the political career of Frank-Walter Steinmeier, the 12th president of the Federal Republic of Germany and one of the most significant social democrats of the last two decades. Sebastian Kohlmann narrates the story how Steinmeier – a representative of the »post-68 generation« – started out as a political actor in the background and ended up as a politician in the frontline of the large political stage of Germany, contradicting the widespread cliché of an administrative official without any visions or passions and instead depicting Frank-Walter Steinmeier as a political spirit with a distinct canon of values and claim of organization, which has been eminent since he was a university student. The biography fathoms the effect Steinmeier has had on his various offices and the new positioning of the SPD in the past two decades. This precise analysis of Frank-Walter Steinmeier's political career draws the profile of a highly political German president.